2018
DOI: 10.1177/0192623318783957
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acute Gene Expression Profiles of Islet Cells Obtained via Laser Capture Microdissection between Alloxan- and Streptozotocin-treated Rats

Abstract: To identify the molecular profiles of islets from alloxan (ALX)- and streptozotocin (STZ)-treated rats, a microarray-based global gene expression analysis was performed on frozen islets isolated via laser capture microdissection. At 6 weeks old, rats were injected with ALX (40 mg/kg) or STZ (50 or 100 mg/kg) and then euthanized 24 hr later. Histopathological analysis showed β-cell necrosis, macrophage infiltration, and islet atrophy. The extent of these changes was more notable in the STZ groups than in the AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Thereby, RNA can be isolated from the entire islet microenvironment, selected regions containing exclusively intact b-cells or infiltrating cells, or even from single b-cells (39). Indeed, laser-capture micro-dissection has been performed in pancreas section of healthy controls, patients with T1D, as well as of several mouse and rat models (37,40,41). Although some of these studies have identified proteins involved in immune cell migration to be upregulated in T1D (42), the focus of these studies was often on other topics and therefore a clear conclusion on the role of chemokines is still missing.…”
Section: Role Of Chemokines In Type 1 Diabetesmentioning
confidence: 99%
“…Thereby, RNA can be isolated from the entire islet microenvironment, selected regions containing exclusively intact b-cells or infiltrating cells, or even from single b-cells (39). Indeed, laser-capture micro-dissection has been performed in pancreas section of healthy controls, patients with T1D, as well as of several mouse and rat models (37,40,41). Although some of these studies have identified proteins involved in immune cell migration to be upregulated in T1D (42), the focus of these studies was often on other topics and therefore a clear conclusion on the role of chemokines is still missing.…”
Section: Role Of Chemokines In Type 1 Diabetesmentioning
confidence: 99%